2017
DOI: 10.1007/s11060-017-2457-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the DEPDC1 oncoantigen in malignant glioma and brain tumor initiating cells

Abstract: DEP domain containing 1 (DEPDC1) is a novel oncoantigen expressed in cancer cells, which presents oncogenic activity and high immunogenicity. Although DEPDC1 has been predicted to be a useful antigen for the development of a cancer vaccine, its pathophysiological roles in glioma have not been investigated. Here, we analyzed the expression and function of DEPDC1 in malignant glioma. DEPDC1 expression in glioma cell lines, glioma tissues, and brain tumor initiating cells (BTICs) was assessed by western blot and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Previous studies have indicated that DEPDC1 is elevated in several types of cancer and is implicated in tumorigenesis (6)(7)(8)(9)(10). It has also been revealed that DEPDC1 is upregulated in HCC tissue and may therefore be an independent predictor of HCC (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that DEPDC1 is elevated in several types of cancer and is implicated in tumorigenesis (6)(7)(8)(9)(10). It has also been revealed that DEPDC1 is upregulated in HCC tissue and may therefore be an independent predictor of HCC (11).…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily expressed in the testis and is not detected in other normal human tissues (6). Recently, several studies revealed that DEPDC1 was upregulated in many tumor types, indicating its important role in tumorigenesis (7)(8)(9)(10). For example, DEPDC1 was upregulated in bladder carcinogenesis and the inhibition of DEPDC1 via small-interfering RNA (siRNA) significantly suppressed the growth of bladder cancer cells (7).…”
Section: Introductionmentioning
confidence: 99%
“…The role of DEPDC1B in prostate cancer was reported by Huang et al DEPDC1B expression significantly upregulated the level of cancer tissue and its mRNA in prostate gland could be used as an independent prognostic indicator for survival rate of prostate cancer patients [25]. In addition, Kikuchi et al found that inhibition of endogenous DEPDC1 expression by small interfering RNA (siRNA) inhibits GBM cell viability and induces apoptosis through NF-κB signaling [26]. Therefore, we set out to explore the effects of DEPDC1B in GBM.…”
Section: Discussionmentioning
confidence: 93%
“…EP300, an apoptosis-associated transcription factor, has been shown to be downregulated in meningioma when compared to normal arachnoid 27 though it's role in meningioma prognostication is not well understood. While DEPDC1 has not been studied in meningioma, it is a known regulator of NFkB signaling and is overexpressed in multiple cancers such as glioma, breast cancer, and nasopharyngeal cancer, having been proposed as a potential therapeutic target in each [28][29][30] . Similarly, the roles of RUNX1, STAT5, and TWIST1 in meningioma remain poorly understood, and could represent novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%